Tourism forecasting in Pahang: an application of homestay by using box-jenkins approach - Noratikah, Abu; Megat Muhammad Afif, Megat Muainuddin (Universiti Malaysia Pahang, 2018)
Tourism forecasting can lead to important elements in tourism industry to ensure that each investment by individuals, companies and government was worth it. From economy perspective, homestay is a growing business nowadays and can be an important indicator to the tourism industry. It also generates income revenue to the owner and also surrounding communities. This paper applied Box-Jenkins (ARIMA) method to make analysis and forecast for the number of domestics tourist used homestay in Pahang. This method much accurate for short and long term forecasting with high frequency of data. Results obtained by applying the proposed model and numerical calculation shows that it is effective for forecasting the number of homestay used by domestic’s tourist and the number of homestay used also increase.